ECONOMIC ASPECTS OF THE ORGANIZATION OF FREIGHT TRANSPORTATION IN THE RAILWAY INDUSTRY - Kurambaev Alisher Saburbaevich (International Scientific and Current Research Conferences, 2024)
The railway industry plays a pivotal role in the global transportation of goods, providing a cost-effective and environmentally friendly mode of freight transport. The economic aspects of organizing and optimizing freight transportation within the railway industry have become increasingly important in recent years. This scientific article explores the key economic factors that influence the organization of freight transportation in the railway sector, focusing on efficiency, sustainability, and competitiveness. By analyzing the economic dynamics within the industry, we aim to shed light on the challenges and opportunities for railway companies and policymakers to enhance the efficiency and profitability of this critical sector.